2019
DOI: 10.1007/s41109-019-0140-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards intelligent complex networks: the space and prediction of information walks

Abstract: In this paper we study the problem of walk-specific information spread in directed complex social networks. Classical models usually analyze the “explosive” spread of information on social networks (e.g., Twitter) – a broadcast or epidemiological model focusing on the dynamics of a given source node “infecting” multiple targets. Less studied, but of equal importance is the case of single-track information flow, wherein the focus is on the node-by-node (and not necessarily a newly visited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this paper we developed and explored novel unipartite projections of the standard bipartite network that connects physicians and their patients. This work was motivated by the historical disregard shown to the time-order of patient visits with their physicians in the construction of shared-patient networks and makes use of the underlying referral path information (An et al, 2018b(An et al, ,a, 2019 that is lost (or neglected) in the formation of the traditional patient-physician bipartite network. We found that referral paths contain substantial information that can be used to better distinguish the one-mode networks from one another thereby enhancing the potential to discover relationships of network features to important health variables compared to what is possible with networks based on currently-used undirected projections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper we developed and explored novel unipartite projections of the standard bipartite network that connects physicians and their patients. This work was motivated by the historical disregard shown to the time-order of patient visits with their physicians in the construction of shared-patient networks and makes use of the underlying referral path information (An et al, 2018b(An et al, ,a, 2019 that is lost (or neglected) in the formation of the traditional patient-physician bipartite network. We found that referral paths contain substantial information that can be used to better distinguish the one-mode networks from one another thereby enhancing the potential to discover relationships of network features to important health variables compared to what is possible with networks based on currently-used undirected projections.…”
Section: Discussionmentioning
confidence: 99%
“…Networks encoding the relationships between physicians and patients, and also between physicians (through shared patients) increasingly are used for research in medicine and health care (An et al, 2018b(An et al, ,a, 2019Barnett et al, 2011). Patient-physician interactions naturally give rise to a bipartite network connecting physicians (on one "side") to the patients that they treat (on the other "side") (see Figure 1 (L)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A graph neural network was trained by Lu and Uddin (2021) using a variety of features to predict the development of chronic diseases. An, O'Malley, and Rockmore (2019) used a combination of multiple metrics to develop a predictive model of the next service a patient is likely to access.…”
Section: Patient Treatmentmentioning
confidence: 99%
“…One area that sought to extend the use of network analysis from descriptive to predictive applications was categorised as patient treatment. An et al (2019) used a variety of network metrics to create a predictive model of the next service that a patient was likely to access. A state-of-the-art example of prediction using networks was seen from Lu and Uddin (2021).…”
Section: Summary Of Key Findingsmentioning
confidence: 99%